KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA PADA MATERI LUAS BANGUN DATAR DIKAJI DARI GAYA KOGNITIF - Nia Kristiani; Edy Yusmin; Munaldus Munaldus; Ahmad Yani T; Dona Fitriawan (Jurnal AlphaEuclidEdu, 2023)
This study aims to describe the talent of SMP Negeri 02 Banyuke Hulu class VII students who have field independent and field dependent cognitive styles in thinking mathematically and creatively about the subject matter. Descriptive qualitative is the method used in this research. Six seventh grade students of SMP Negeri 02 Banyuke Hulu were used as research subjects. Geft test to assess cognitive style and a description test consisting of three questions and three stages, namely data reduction, data presentation, and conclusion drawing, were used to analyze the data. The results showed that two students with field-independent cognitive style can achieve both indicators of fluency and flexibility, but one other student with the same cognitive style can only fulfill one indicator, namely flexibility. It is known that two students can fulfill three criteria of field dependent cognitive style, namely fluency, flexibility, and novelty. Two indicators namely fluency and flexibility can be met by one additional student who has a field dependent cognitive style. Thus students of grade 7 SMP Negeri 02 Banyuke Hulu with cognitive style field independent and field dependent have the ability to think creatively mathematically in the context of flat buildings. In working on description form problems there are still some difficulties students solve problems on the material of flat area.